Pengaruh Struktur Kepemilikan, Likuiditas, Leverage, dan Aktivitas (TATO) Terhadap Financial Distress Perusahaan Industri Barang Konsumsi yang Terdapat Pada Bursa Efek Indonesia - Yuriani Yuriani; Merry Merry; Jennie Jennie; Muhammad Ikhsan; Namira Ufrida Rahmi (COSTING : Journal of Economic, Business and Accounting, 2020)
Financial Distress is indicated as company’s financial decrease which can be caused by various circumstances. Identifying financial distress is important to do since financial distress that occurs continuously will lead to company failure. This research is useful to see the impact of Ownership Structure, Liquidity, Leverage, and Activity in predicting Financial Distress to the sector consumer goods companies listed in Indonesia Stock Exchange. The independent variable used is Ownership Structure, Current ratio, Debt ratio, and Activity (TATO). While the dependent variable used is Financial Distress. The sample in this research involve 27 companies was taken by Purposive Sampling technique by determining 3 criterias within a span of 5 years, so the amount of research data was obtained as many as 135. This study use quantitative research. The results of this research using multiple linear regression analysis concluded Ownership Structure, Liquidity, and Activity have positive impact on Financial Distress. While Leverage is the only variable whichhas no significant influence on Financial Distress. Keywords : Ownership Structure, Liquidity, Leverage, Activity, Financial Distress.